Experimental ex vivo traumatic intrusion in the mandibular incisors of the farm pig, Sus scrofa. Issue 6 (20th April 2014) - Patterson, Amanda; Popowics, Tracy
Abstract Background/Aim Traumatic intrusion of incisor teeth occurs frequently in young children, as well as in teens and adults; however, the biological mechanisms promoting negative sequelae or recovery are not well understood (Oral Surg Oral Med Oral Pathol Oral Radiol Endod 2009;107:493 and Vital Health Stat 11 2007;248:1). Modeling intrusive trauma and post‐traumatic healing in an animal model offers the opportunity to define these biological mechanisms and to inform the design of treatments. The objective of this study was to investigate the pig, Sus scrofa, as a model for intrusive trauma, using an in vitro approach. Materials and Methods Mandibular segments from ex vivo farm pigs were bisected and primary central incisors were prepared to either receive axial traumatic loads or to serve as non‐intruded controls. A class 2 lever modeled traumatic impact to the incisors. Damage to the periodontal support in intruded and control specimens (n = 10) was evaluated through compression testing and comparison of elastic moduli. Incisor displacement was measured on X‐ray images taken before and after trauma, and following compressive tests. Results Lingual x‐rays showed a mean postinjury displacement of the incisor root of 3.81 ± 1.87 mm. With compression testing, the root length embedded in bone increased in traumatized and non‐traumatized teeth by 2.9 mm and 0.81 mm, respectively (P = 0.03). The intrusion group Young's modulus was significantly lower than the control group (4452 vs 7704 Mpa; P = 0.05). Conclusion In vitro modeling of traumatic intrusion resulted in damage to the periodontal support of central incisors and axial tooth displacement. Pig incisors offer an important model for further study of incisor trauma.